PERBEDAAN KADAR N-TERMINAL PRO BRAIN NATRIURETIC PEPTIDE PLASMA BERDASARKAN LUARAN FUNGSIONAL STROKE ISKEMIK AKUT - Gunawan Septa Dinata; Syarif Indra (NEURONA, 2021)
systemic vascular system when ischemic stroke occur. BNP is secreted by myocardial and causes vasodilatation, natriuresisand diuresis. Increase myocardial wall pressure triggers pre-proBNP synthesis in myocardial. Pre-proBNP then wasdivided into an active form (BNP1-32) and inactive amino-terminal fragmen (NT-proBNP).Objective: To evaluate the differences of plasma N-terminal pro brain natriuretic peptide (NT-proBNP) levels inacute stroke ischemic based on functional outcome of acute ishemic stroke patient.Methods: This is an observational study that was conducted at neurology ward of M. Djamil Padang Hospitalfor acute stroke ischemic patients. The sample was selected by consecutive sampling method. Functional outcome wasassessed by Modified Rankin Scale (mRS). Plasma NT-proBNP levels were analyzed by enzyme-linked immunosorbentassay (ELISA).Results: The mean level of plasma NT-proBNP of acute ischemic stroke patient was 287.8±84.2 pg/mL. Data wasanalyzed using ????ruskal ????allis and the result showed that there is a significant differences in plasma NT-proBNP (????????2hours) levels based on functional outcome of acute ischemic stroke, p value ????0.05 (p????0.018).Discussion: There is an differences in acute phase of NTproBNP plasma level with functional outcome ischaemicstroke.Keywords: BNP, functional outcome, NT-proBNP